Egas Moniz: twice a double life - Bertolote,José Manoel (2015)
Egas Moniz is credited with the discovery in 1927 of radioarteriography, for which he was, on three occasions, nominated for the Nobel Prize, and in all three denied the award. In 1949 he was awarded the Nobel Prize for Medicine for having designed leucotomy, a brain surgery to treat some forms of severe metal disorders. He was also an successful politician and accomplished statesman.